Pre‐hospital administration of ticagrelor in diabetic patients with ST‐elevation myocardial infarction undergoing primary angioplasty: A sub‐analysis of the ATLANTIC trial. Issue 7 (9th October 2018) - Fabris, Enrico; van't Hof, Arnoud; Hamm, Christian W.; Lapostolle, Frédéric; Lassen, Jens Flensted; Goodman, Shaun G.; ten Berg, Jurriën M.; Bolognese, Leonardo; Cequier, Angel; Chettibi, Mohamed; Hammett, Christopher J.; Huber, Kurt; et al.
Abstract: Objective: We investigated, in the contemporary era of ST‐elevation myocardial infarction (STEMI) treatment, the influence of diabetes mellitus (DM) on cardiovascular outcomes, and whether pre‐hospital administration of ticagrelor may affect these outcomes in a subgroup of STEMI patients with DM. Background: DM patients have high platelet reactivity and a prothrombotic condition which highlight the importance of an effective antithrombotic regimen in this high‐risk population. Methods: In toal 1, 630 STEMI patients enrolled in the ATLANTIC trial who underwent primary percutaneous coronary intervention (PCI) were included. Multivariate analysis was used to explore the association of DM with outcomes and potential treatment‐by‐diabetes interaction was tested. Results: A total of 214/1, 630 (13.1%) patients had DM. DM was an independent predictor of poor myocardial reperfusion as reflected by less frequent ST‐segment elevation resolution (≥70%) after PCI (OR 0.59, 95% CI 0.43–0.82, P < 0.01) and was an independent predictor of the composite 30‐day outcomes of death/new myocardial infarction (MI)/urgent revascularization/definite stent thrombosis (ST) (OR 2.80, 95% CI 1.62–4.85, P < 0.01), new MI or definite acute ST (OR 2.46, 95% CI 1.08–5.61, P = 0.03), and definite ST (OR 10.00, 95% CI 3.54–28.22, P < 0.01). No significant interaction between pre‐hospital ticagrelor vs in‐hospital ticagrelor administration and DM was present for the clinical, electrocardiographic and angiographic outcomes as well as for thrombolysis in myocardial infarction major bleeding. Conclusions: DM remains independently associated with poor myocardial reperfusion and worse 30‐day clinical outcomes. No significant interaction was found between pre‐hospital vs in‐hospital ticagrelor administration and DM status. Further approaches for the treatment of DM patients are needed. CLINICAL TRIAL REGISTRATION: clinicaltrials.gov identifier: NCT01347580.